DNA MARKER-ASSISTED AND MORPHOLOGICAL SELECTION ON BC3 GENOTYPES SHORTCUT THE INTROGRESSION OF CMV TOLERANCE GENES ON CHILI PEPPER - Herison, Catur; Winarsih, Sri; Handayaningsih, Merakati; Rustikawati, Rustikawati (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
Superior hybrid and CMV tolerant cultivar development requires a pair of high heterobeltiosis parents and both of which are CMV tolerant. Gene introgression has to be accomplished if the tolerance does not exist in the parents. This research was objected to employ DNA markers and morphological traits on identifying the most resemble BC3 CMV tolerant individuals to their recurrent parents to shortcut the backcrossing cycle. This research used fifteen BC3 populations generated from crosses of hybrid parents PBC1354 and PBC378 with tolerant parents of C1024, C1042 and C1043. The BC3 populations were previously selected for their CMV tolerance and were characterized by RAPD technique and morphological traits. Selection by means of both RAPD marker and morphological traits identified BC3 individuals 99.9% resemble to their recurrent parent. Genotypes B3A24-20, B3A29-13, B3A29-22, B3B12-13, B3B37-9, B3B12-25, B3C16-5, B3C16-16, B3C34-18 99.9% were similar to PBC378, and B3D11-8, B3D11-17, B3D38-5, B3E12-17, B3E20-22, B3E31-19 were 99.9% similar to PBC1354. Those genotypes were both similar to their recurrent parent and tolerance to CMV. The employed strategy shortcut CMV tolerance genes introgression through a backcross breeding.